Wadi Al-Qelt: Geomorphological Study – Palestine - Owais, Abdalla Hussein; Al-Khateeb, Mohammad Anwar; Al-Attal, Walaa Mohamed Nabeel; Zain, Dalal Mustafa (Journal of natural sciences, life and applied sciences, 2022)
The study aimed to examine the geological and climatic characteristics of Wadi Al-Qelt to identify their impact on its morphological characteristics. The valley is located on the eastern slopes of the Jerusalem mountains located within the mountains and plateaus of central Palestine, where hot weather, dry winds, rain fluctuations, and low humidity are the essential characteristics of this valley. Therefore, the climatic and geological characteristics clearly reflected its morphological characteristics. In addition, the study sheds light on ways to protect it from geomorphological risks and how to reduce them because of the natural importance of this valley represented in its origin and the path associated with the emergence of the Jordan Valley (Ghawr Al-Urdun) region and the eastern drainage network in Palestine, as well as its historical, geographical and religious importance.The historical, descriptive-analytical, and cartographic method was used to achieve the goals. The research concluded several results, the most important of which are: that the valley constitutes a vital tourist and archaeological component, and the processes of weathering and erosion play a role in the diversity of its soil, in addition to the decline in the rate of precipitation that contributed to the increase in drought rates, and the decline in the intensity of drought. The vegetation cover and the research recommended the necessity of sustainable development projects to preserve this distinguished site.
Keywords: Wadi Al-Qelt; Eastern slopes; Geomorphological characteristics; mountains; plateaus of central Palestine